Generation of RUNX3 knockout pigs using CRISPR/Cas9‐mediated gene targeting. (1st October 2016) - Kang, J‐T; Ryu, J; Cho, B; Lee, E‐J; Yun, Y‐J; Ahn, S; Lee, J; Ji, D‐Y; Lee, K; Park, K‐W
Contents: Pigs are an attractive animal model to study the progression of cancer because of their anatomical and physiological similarities to human. However, the use of pig models for cancer research has been limited by availability of genetically engineered pigs which can recapitulate human cancer progression. Utilizing genome editing technologies such as CRISPR/Cas9 system allows us to generate genetically engineered pigs at a higher efficiency. In this study, specific CRISPR/Cas9 systems were used to target RUNX3, a known tumour suppressor gene, to generate a pig model that can induce gastric cancer in human. First, RUNX3 knockout cell lines carrying genetic modification (monoallelic or biallelic) of RUNX3 were generated by introducing engineered CRISPR/Cas9 system specific to RUNX3 into foetal fibroblast cells. Then, the genetically modified foetal fibroblast cells were used as donor cells for somatic cell nuclear transfer, followed by embryo transfer. We successfully obtained four live RUNX3 knockout piglets from two surrogates. The piglets showed the lack of RUNX3 protein in their internal organ system. Our results demonstrate that the CRISPR/Cas9 system is effective in inducing mutations on a specific locus of genome and the RUNX3 knockout pigs can be useful resources for human cancer research and to develop novel cancer therapies.